Staphylococcus aureus infection in children: diagnosis and treatment in the context of antibiotic resistance spread - Yu.K. Bolbot; T.A. Bordii; S.V. Alifanova; M.V. Kalichevska (Zaslavsky O.Yu., 2022)
The emergence and rapid spread of methicillin-resistant Staphylococcus aureus (MRSA) isolates in the world significantly complicated the treatment and changed the approaches to the diagnosis of staphylococcal infections in children. Staphylococcus aureus is a widespread microorganism dangerous for humans. A wide range of virulence factors the list of which is still being added allows it to quickly enter the body through damaged barriers and cause local and invasive infections, toxin-mediated diseases, as well as persist for a long time. Currently, two fundamentally different variants of MRSA are distinguished: health care-associated and community-acquired. Health care-associated MRSA are resistant to a greater number of antimicrobial agents, while community-acquired MRSA isolates are characterized by recurrent infections and a more severe course of invasive diseases. In addition, MRSA is gradually developing resistance to those antibacterial agents that were the basis of treatment for these infections, primarily clindamycin and vancomycin. All this requires global and regional monitoring of MRSA spread in different variants of staphylococcal infections and the sensitivity of the isolates found to antibiotics in order to optimize empiric and pathogen-specific antibacterial therapy. The article presents data on the activity of various antimicrobial agents against S.aureus, analyzes the available information on the prevalence of MRSA in Ukraine and the results of local monitoring for antibiotic resistance, which turned out to be unidirectional with global trends. Clinical and laboratory criteria for diagnosis of local staphylococcal infections, invasive and toxin-mediated diseases in childhood were presented. Treatment of S.aureus infections involves the necessary surgical interventions and antibacterial therapy considering current epidemiological situation on the spread of MRSA and their sensitivity to antimicrobial agents. Further studies are needed to determine the prevalence of MRSA in children in Ukraine to develop antibacterial therapy algorithms for various types of staphylococcal infections.